Chinese etiquette and ethics in business - De Mente, Boye. (Lincolnwood, Ill., USA : NTC Business Books, 1994)
The land and the people. The historical perspective. The awakening dragon. Living in a beehive society. Working in a beehive society. New rules and guidelines. Other cultural factors affecting business...
Keywords: Business ethics; Business etiquette; Business ethics; Business etiquette -- China; Industrial management -- China; National characteristics, Chinese